INOKULASI MIKORIZA DAN DISTRIBUSI ASIMILAT PADA TANAMAN KEDELAI - Sri Suryanti; Didika Indradewa; Jaka Widada (AGROISTA : Jurnal Agroteknologi, 2017)
Soybean is a cheap source of vegetable protein. Effort to increase of soybean production have constrained the narrowness of fertile land. One way to increase soybean production in less fertile land is inoculation of mycorrhizal. The objective of this study are to conduct effect of mycorrhizal inoculation on physiological of soybean cultivars. The 18 x 2 factorial experiment was set up in completely randomize design using three replications during June to October 2013. The eighteen soybean cultivars (Grobogan, Burangrang, Sibayak, Kaba, Tanggamus, Anjasmoro, Argomulyo, Wilis, Panderman, Ijen, Baluran, Galunggung, Petek, Garut, Gepak Kuning, Malabar, Seulawah, Sinabung) were assigned as the first factor. The second factor was mycorrhizal inoculation with without mycorrhizal inoculation and mycorrhizal inoculation. Data were recorded for dry weight of shoot, dry weight of root, dry weight of plant, root shoot ratio at 56 days after planting, and harvest index at 84 days after planting. The result showed that mycorrhizal inoculation significantly increased the dry weight of shoot, dry weight of root, dry weight of plant and harvest index but significantly decreased of root shoot ratio.